2023
DOI: 10.1371/journal.pone.0281870
|View full text |Cite
|
Sign up to set email alerts
|

Impact of foreign direct investment on income inequality: Evidence from selected Asian economies

Abstract: The United Nations lists 17 Sustainable Development Goals for Agenda 2030, one of which is SDG-10, which focuses on eradicating inequality and addressing critical regional and global challenges. The fight against income inequality is heavily dependent on foreign direct investment all over the world. In this connection, the present study aimed to investigate the individual and interactive impact of foreign direct investment, human capital, and economic growth on income inequality by employing the interactive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Using OLS and time series data techniques, Abubakar (2020) observed that institutional quality responds to economic growth positively. This finding also supports Yuldashev et al (2023) who found a positive relationship between institutional quality and economic growth. Using GMM model for 113 economies, Khan and Hanif (2020) found that institutional quality affects economic while they found a negative relationship between inflation and economic growth.…”
Section: Review Of Empirical Studiessupporting
confidence: 88%
“…Using OLS and time series data techniques, Abubakar (2020) observed that institutional quality responds to economic growth positively. This finding also supports Yuldashev et al (2023) who found a positive relationship between institutional quality and economic growth. Using GMM model for 113 economies, Khan and Hanif (2020) found that institutional quality affects economic while they found a negative relationship between inflation and economic growth.…”
Section: Review Of Empirical Studiessupporting
confidence: 88%
“…The results of Panel ARDL long run and short run are presented in Table 2. In this table, the coefficient of urbanization variables concludes a positive relationship between urbanization and Income inequality (Cho & Ramirez, 2016;Yuldashev et al, 2023). This effect may be due to the reason that the cost of living can go up as a result of urbanization, which can manifest itself in higher rents, overall property prices, and overall costs.…”
Section: Resultsmentioning
confidence: 88%
“…Using the interactive model, Yuldashev et al (2023) sought to study the individual as well as the interactive influence that economic growth, human capital, and foreign direct investment have on income inequality. In addition, an approach known as the Augmented Mean Group (AMG) was utilized in the research project to achieve correct outcomes in estimating.…”
Section: Introductionmentioning
confidence: 99%
“…Hongxing et al, (2021) analyzed heterogeneous evidence from African countries using cross-sectional dependency from 1990 to 2018. Among these techniques, FMOLS and DOLS are extensively applied to estimate the nexus by Adebayo et al (2022), Karimi Alavijeh et al (2023, Yuldashev et al (2023); and for the case of BRICS, EU, Asian and OECD economies, respectively. Moreover, Chenyun et al ( 2022) examined BRI countries under the augmented mean group estimator with novel results.…”
Section: Literature Reviewmentioning
confidence: 99%